Comparative assessment of tuberculosis vaccination in children with perinatal exposure to HIV and without it - V. A. Kukarkina; A. A. Golubkova; A. S. Podymova; A. A. Kukarkina (Туберкулез и болезни лёгких)
The objective of the study is to assess the scope and timing of tuberculosis vaccination in children with perinatal exposure to HIV, to determine the effectiveness of vaccination by the scarsize and results of Mantoux test in 12 month safter vaccination.Subjects and methods. Documents on vaccination (Form no.063/u) and case histories (Form no.112/u) of 216 children with perinatal exposure to HIV were analyzed. The control group consisted of 100 children of the same age group born by HIV negative mothers. In this study, epidemiological (descriptive-evaluative, andanalytical) and statistical methods of research were applied.Results. The proportion of children vaccinated against tuberculosis in the maternity ward in the group with perinatal exposure to HIV made 74/196, and in the control group – 82/99, pχ2 < 0.01. The main reasons for the lack of vaccination were the failure to undergo the three-stage preventive chemotherapy of perinatal HIV infection (35%), neonatal pathology and prematurity (42%). No difference was found in the frequency of the vaccination scar formation and results of Mantoux test (in 12 months after vaccination) in children exposed to HIV and children from the control group (p > 0.05).65.3% of children exposed to HIV developed the vaccination scar and demonstrated post-vaccination allergies (55.3%) in 12 months after vaccination and there was no difference from children of the control group.